THE ROLE OF THE FOOD AND DRUG ADMINISTRATION (BPOM) IN MONITORING COSMETIC PRODUCTS CONTAINING HARMFUL SUBSTANCES IN PALANGKA RAYA - Dea Helmilia Putri; Abdul Khair; Novita Angraeni (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the role of the Food and Drug Administration (BPOM) in monitoring cosmetic products containing hazardous substances in Palangka Raya. The research problem raised in this study is how BPOM monitors hazardous cosmetics and what challenges are faced in carrying out this task. The objective of this study is to examine the challenges faced by BPOM in carrying out the monitoring of hazardous cosmetics in Palangka Raya and to provide recommendations for improving the effectiveness of monitoring. This study uses a descriptive qualitative method, with an empirical juridical approach combining secondary data analysis and direct observation of monitoring practices. The results show that although BPOM has carried out various monitoring efforts, such as cyber patrols, distribution inspections, and public education, the main challenges faced include environmental factors, limited human resources, and lack of public awareness about the dangers of illegal cosmetics. This study recommends the need for better cooperation between BPOM, local government, and the public, as well as increased use of technology and educational programs to strengthen the monitoring of hazardous cosmetics in Palangka Raya.